A research on the application of fuzzy iteration clustering in the water conservancy project. (10th May 2017) - Lu, Shibao; Shang, Yizi; Li, Yuwen
Abstract: Water conservancy project bidding involves many aspects including nature, society, economy, and environment. In water conservancy project bidding evaluation, both quantitative and qualitative indexes are involved; moreover, different targets are often incommensurable and compete with each other. Scientific decision-making in bidding evaluation is key to linking the stages of project bidding; selecting an appropriate contractor is not only conducive to improving the project quality, but also helpful to achieve the goal of saving on investments. This paper intends to study the problem of multi-target group decision-making in project bidding processes via the use of the mathematical method of fuzzy clustering. Bidder 3 is finally chosen as the most suitable contractor for the construction of this project by determining the score matrix and index weight vector of the four bidders concerned. Results have indicated that the aforementioned method is more reasonable and reliable; thus, the bidding evaluation decision is more scientific.